MAGNETISM OF WHITE DWARFS (intermediate results of a survey for kilogauss magnetic fields in white dwarfs) - Valyavin, G.; Bagnulo, S.; Fabrika, S.; Reisenegger, A.; Wade, G. A.; Han, Inwoo; Monin, D. (Одеські астрономічні публікації, 2017)
We shortly present intermidiate results of a survey for weak magnetic fields among degenerate stars (white dwarfs and hot subdwarf stars). Kilogauss upper limits of longitudinal magnetic fields are presented for several brightest DA white dwarfs and new candidates to magnetic degenerates are found. We discuss our findings in the frame of 25fractional incidence of white dwarf magnetism in the kilogauss region. The complete version of this presentation will be published in the Astrophysical Journal.